Didactic problem: Teaching and methods in volleyball - Altavilla, G. (Journal of Human Sport & Exercise, 2021)
Didactic problem for the teacher is enormous since there is not only one method, but there are methods that each teacher must adapt with his own experience to the different needs of the students and the environmental context. As part of teaching of motor skills in volleyball, when we talk about method we generally refer to a series of intentional and organized actions that are implemented to achieve the set objectives, through the choice and use of means and contents that can favour motor learning. The teaching action of the teacher will be all the more effective the more adequate the working method is adopted. The term "method" is often connected to the terms "deductive" and "inductive", therefore the distinction made between directive and non-directive style places the accent on the direct intervention of the teacher, while the other on the assumption by students of many aspects of the teaching function. Teaching methods find their origin in the two classic forms of deduction (managerial style) and induction (non-directive style). The teacher must know how to adopt different styles and methods according to the didactic needs, as there are no better styles and methods than others but choices suitable for achieving different objectives.